Complications of Uterine Fibroids and Their Management, Surgical Management of Fibroids, Laparoscopy and Hysteroscopy versus Hysterectomy, Haemorrhage, Adhesions, and Complications - Liselotte Mettler; Thoralf Schollmeyer; Andrea Tinelli; Antonio Malvasi; Ibrahim Alkatout (Obstetrics and Gynecology International)
A critical analysis of the surgical treatment of fibroids compares all available techniques of myomectomy. Different statistical analyses reveal the advantages of the laparoscopic and hysteroscopic approach. Complications can arise from the location of the fibroids. They range from intermittent bleedings to continuous bleedings over several weeks, from single pain episodes to severe pain, from dysuria and constipation to chronic bladder and bowel spasms. Very seldom does peritonitis occur. Infertility may result from continuous metro and menorrhagia. The difficulty of the laparoscopic and hysteroscopic myomectomy lies in achieving satisfactory haemostasis using the appropriate sutures. The hysteroscopic myomectomy requires an operative hysteroscope and a well-experienced gynaecologic surgeon.